Diabetic ketoacidosis associated with outpatient treatment using continuous subcutaneous insulin infusion. Issue 693 (July 1983) - Boulton, A. J.; Knight, G.; Drury, J.; Ward, J. D.
Abstract : The occurrence of ketoacidosis in out-patient diabetics treated with continuous subcutaneous insulin infusion (CSII) has received little attention. We report two such cases of ketosis, each precipitated by infection and occurring in patients previously well controlled on CSII. This report illustrates that the risk of ketoacidosis is ever present in insulin-treated patients, whether the insulin is infused by pump or injected intermittently.